Chromatogram libraries improve peptide detection and quantification by data independent acquisition mass spectrometry - Brian C. Searle (Nature Portfolio, 2018)
Data-independent acquisition (DIA)-based proteomics often relies on mass spectrum libraries from data-dependent acquisition experiments. Here, the authors present a method to generate DIA-based chromatogram libraries, enabling DIA-only workflows and detecting more peptides than with spectrum libraries alone.